The social and family evaluation (SAFE) scale for caregivers of individuals with disorders of consciousness: preliminary results - Magnani, F. G.; Cacciatore, M.; Barbadoro, F.; Ippoliti, C.; Sattin, D.; Magliacano, A.; Draghi, F.; De Nisco, A.; Hakiki, B.; Cecchi, F.; Spinola, M.; Estraneo, A.; et al. (Neurological sciences, 2025)
Background Caregivers’ involvement in the diagnostic and monitoring processes of the level of consciousness of patients with Disorders of Consciousness (DoC) is strongly encouraged by international guidelines, as current literature suggests a better chance to detect behavioural responses when caregivers are involved in clinical assessments. Since caregivers’ involvement during clinical assessments can be difficult, the Social And Family Evaluation (SAFE) scale has been recently proposed as a standardised tool that caregivers can autonomously use to collect their opinions about the level of consciousness of patients with DoC, based on the behaviours manifested by the patients in a given time-window. Objective Providing preliminary results concerning SAFE adoption. Methods 22 patients with DoC were assessed through the Coma Recovery Scale-revised (CRS-r), while their caregivers filled-in the SAFE. Results The SAFE showed a very high internal consistency, very high test-retest reliability, and high criterion validity when correlated to the CRS-r total score. Moreover, in line with the literature, the SAFE allowed the detection of some behaviours indicative of a higher level of consciousness than those detected by clinicians through the CRS-r in more than half of the sample. Conclusion Overall, these preliminary data are promising for the adoption of the SAFE to collect the opinions of the caregivers about the level of consciousness of patients with DoC, especially in those settings where it would be otherwise difficult to monitor the patients, such as long-term care structures and at home, as a tool for telemedicine allowing the monitoring of patients in remote settings.